Free Maternal Healthcare Programme under the Successful Delivery Programme in Jigawa State, Nigeria - Abdulkadir, Muhammad; Bn Rainis, Ruslan; Uba Mohammed, Murtala (International Journal of Psychosocial Rehabilitation, 2019)
In the state effort reduce the number of maternal deaths, a free child and maternal healthcare programme were introduced called Successful delivery. This main aim of this research is to evaluate if women registered with the programme had a better chance of accessing the services in the state. A cross-sectional quantitative study involving household interviews of all women of the reproductive age group (15–49 years) residing in Jigawa state from February to April 2019. Logistic regression analysis at 95% confidence interval was used to determine the independent associations between the scheme and use of antenatal care, hospital delivery and postnatal care services. successful delivery program influenced the antenatal care visit as women registered with the schemes are more likely to have maximum of six visit 39.5 times than those who did not and also more likely to have four visit 2.6 times than those without scheme. Hospital delivery is also attached to the scheme as women registered with the scheme is 5.3 times likely to deliver at hospital when compared to those with not. Successful delivery program influences antenatal care visit and hospital base delivery. Nevertheless, many of the pregnant women after delivery did not attend postnatal care.